Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1747-4949.2009.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Prehospital and In-Hospital Delay Times in Acute Stroke Care

Abstract: The purpose of this study was to systematically review and summarize prehospital and in-hospital stroke evaluation and treatment delay times. We identified 123 unique peer-reviewed studies published from 1981 to 2007 of prehospital and in-hospital delay time for evaluation and treatment of patients with stroke, transient ischemic attack, or stroke-like symptoms. Based on studies of 65 different population groups, the weighted Poisson regression indicated a 6.0% annual decline (p<0.001) in hours/year for prehos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
183
4
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(206 citation statements)
references
References 106 publications
6
183
4
9
Order By: Relevance
“…While prehospital delays have declined significantly from 1981 to 2007, no appreciable changes for in-hospital delay times were observed during the same period. 4 A recent systematic review reported that inhospital times are consistently longer than the recommended NINDS goals. 5 These goals, published in 1996, recommend the following: 10 minutes from door to ED evaluation, 15 minutes from door to neurologist notification, 25 minutes from door to initiation of CT scan, 45 minutes from door to CT interpretation, and 60 minutes from door to tPA administration.…”
mentioning
confidence: 99%
“…While prehospital delays have declined significantly from 1981 to 2007, no appreciable changes for in-hospital delay times were observed during the same period. 4 A recent systematic review reported that inhospital times are consistently longer than the recommended NINDS goals. 5 These goals, published in 1996, recommend the following: 10 minutes from door to ED evaluation, 15 minutes from door to neurologist notification, 25 minutes from door to initiation of CT scan, 45 minutes from door to CT interpretation, and 60 minutes from door to tPA administration.…”
mentioning
confidence: 99%
“…15 The use of such strategies is likely one of the core reasons for the observed decline in prehospital delays to accessing thrombolytic therapy over the past decade. 13 Functional disability and mortality rates in telestroke treated patients are similar to those in patients treated at tertiary care centres. 29 Similarly, symptomatic hemorrhagic transformation rates are similar when comparing telestroke services with face-to-face stroke care by stroke neurologist.…”
Section: Review Of the Literaturementioning
confidence: 70%
“…Most of the time delay to administering thrombolysis elapses prior to the patient arriving in the Emergency Department. 13 Accordingly, a strong emphasis needs to be placed on identifying the factors contributing to prehospital delays in accessing definitive therapy. Finding ways to diminish or eliminate these factors represents a significant opportunity to improve the outcomes experienced by patients with acute ischemic stroke.…”
Section: Introduction To the Problemmentioning
confidence: 99%
“…The analysis was carried out for the remaining 379 patients, 180 with PHN and 199 without PHN (Figure 1). Median door-to-CT time for the PHN group was 6 min less than for the no-PHN group, which was statistically significant (median [interquartile range: IQR]; 14 [9][10][11][12][13][14][15][16][17][18][19][20][21][22] vs 20 ; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple factors have been identified for in-hospital delays including decision making process, laboratory tests, neurology service arrival and imaging [10][11][12]. Previously, we tried to identify and resolve the issues related to in-hospital latencies in our hospital in Tabriz, Iran.…”
mentioning
confidence: 99%